2014
DOI: 10.1017/s0031182014000110
|View full text |Cite
|
Sign up to set email alerts
|

Parasites as biological tags of marine, freshwater and anadromous fishes in North America from the tropics to the Arctic

Abstract: Parasites have been considered as natural biological tags of marine fish populations in North America for almost 75 years. In the Northwest Atlantic, the most studied species include Atlantic cod (Gadus morhua), Atlantic herring (Clupea harengus) and the redfishes (Sebastes spp.). In the North Pacific, research has centred primarily on salmonids (Oncorhynchus spp.). However, parasites have been applied as tags for numerous other pelagic and demersal species on both the Atlantic and Pacific coasts. Relatively f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 105 publications
1
9
0
1
Order By: Relevance
“…gave the strongest evidence of an effect to the model. Anisakids are the most commonly used parasites for stock differentiation as they are abundant and due to their large size easy to detect [ 18 , 68 , 69 ], which was confirmed in this study. The calculated probabilities to assign the correct origin of a fish according to the presence of an identified parasite species showed that a fish with C .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…gave the strongest evidence of an effect to the model. Anisakids are the most commonly used parasites for stock differentiation as they are abundant and due to their large size easy to detect [ 18 , 68 , 69 ], which was confirmed in this study. The calculated probabilities to assign the correct origin of a fish according to the presence of an identified parasite species showed that a fish with C .…”
Section: Discussionsupporting
confidence: 81%
“…When choosing biological tags to separate fish stocks, genetic structure of parasite populations potentially identify host stock structure or host migration patterns more accurately than classic parasite abundance measurements [ 69 ]. Commonly used markers for population structure analyses are mitochondrial genes such as cox2 (cytochrome oxidase c) with their high substitution rate and maternal inheritance [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fish were sectioned and the alimentary canal, liver, kidney, swim bladder and spleen examined for endoparasites. The excised gastrointestinal tract was carefully sectioned into portions such as oesophagus, intestine and rectum and each portion was then cut open, washed in Petri dish with 0.1% sodium chloride solution and further rinsed with 0.1% sodium bicarbonate to enhance parasite search (Paperna, 1996;Marcogliese, 2011). Trematode cysts from the muscle were manually teased to release the metacercariae, which were (Ezemonye et al, 2008) fixed in hot alcohol-formal-acetate (AFA) and preserved in 70% ethyl alcohol.…”
Section: Parasitofauna Analysismentioning
confidence: 99%
“…Cestodes were stained with aqueous acetocarmine solution (Khalil, 1971). The acanthocephalans were placed in a refrigerator overnight in Petri dishes containing 0.1% sodium chloride solution (this caused the proboscis of the acanthocephalans to extrude) and then preserved in 70% ethyl alcohol (Marcogliese, 2011). Leeches collected from fishes were kept in mentholic water to ensure complete relaxation before fixation in 95% ethyl alcohol (Khalil, 1971).…”
Section: Parasitofauna Analysismentioning
confidence: 99%
“…diese mit der Nahrung aufnehmen. Sowohl in limnischen als auch in brackigen und marinen Lebensräumen ließen sich so unterschiedliche Fischpopulationen mittels ihrer ortstypischen Parasitenfauna nachweisen . Ebenso behalten Fische bei Wechseln zwischen Süß‐ und Salzwasserhabitaten (und vice versa ) im Zuge von Laichwanderungen einen Teil der Parasitenarten ihres Herkunftsgebietes.…”
Section: Neues Wissen üBer Die Wirteunclassified